A Reassessment of ANOVA Reporting Practices: A Review of Three APA Journals - Yuanyuan Zhou (Journal of Methods and Measurement in the Social Sciences, 2018)
Historically, ANOVA has been the most prevalent statistical method used in educational and psychological research and today ANOVA continues to be widely used.  A comprehensive review published in 1998 examined several APA journals and discovered persistent concerns in ANOVA reporting practices.  The present authors examined all articles published in 2012 in three APA journals (Journal of Applied Psychology, Journal of Counseling Psychology, and Journal of Personality and Social Psychology) to review ANOVA reporting practices including p values and effect sizes.  Results indicated that ANOVA continues to be prevalent in the reviewed journals as a test of the primary research question, as well as to test conditional assumptions prior to the primary analysis.  Still, ANOVA reporting practices are essentially unchanged from what was previously reported.  However, effect size reporting has improved.